On the "Tertiary Structure" of Poly‐Carbenes; Self‐Assembly of sp3‐Carbon‐Based Polymers into Liquid‐Crystalline Aggregates. Issue 35 (12th July 2013) - Franssen, Nicole M. G.; Ensing, Bernd; Hegde, Maruti; Dingemans, Theo J.; Norder, Ben; Picken, Stephen J.; Alberda van Ekenstein, Gert O. R.; van Eck, Ernst R. H.; Elemans, Johannes A. A. W.; Vis, Mark; Reek, Joost N. H.; de Bruin, Bas
Abstract The self‐assembly of poly(ethylidene acetate) (st‐PEA) into van der Waals‐stabilized liquid‐crystalline (LC) aggregates is reported. The LC behavior of these materials is unexpected, and unusual for flexible sp3‐carbon backbone polymers. Although the dense packing of polar ester functionalities along the carbon backbone of st‐PEA could perhaps be expected to lead directly to rigid‐rod behavior, molecular modeling reveals that individual st‐PEA chains are actually highly flexible and should not reveal rigid‐rod induced LC behavior. Nonetheless, st‐PEA clearly reveals LC behavior, both in solution and in the melt over a broad elevated temperature range. A combined set of experimental measurements, supported by MM/MD studies, suggests that the observed LC behavior is due to self‐aggregation of st‐PEA into higher‐order aggregates. According to MM/MD modeling st‐PEA single helices adopt a flexible helical structure with a preferred trans‐gauche syn‐syn‐anti‐anti orientation. Unexpectedly, similar modeling experiments suggest that three of these helices can self‐assemble into triple‐helical aggregates. Higher‐order assemblies were not observed in the MM/MD simulations, suggesting that the triple helix is the most stable aggregate configuration. DLS data confirmed the aggregation of st‐PEA into higher‐order structures, and suggest the formation of rod‐like particles. The dimensions derived from these light‐scattering experiments correspond with st‐PEA triple‐helix formation. Langmuir–Blodgett surface pressure–area isotherms also point to the formation of rod‐like st‐PEA aggregates with similar dimensions as st‐PEA triple helixes. Upon increasing the st‐PEA concentration, the viscosity of the polymer solution increases strongly, and at concentrations above 20 wt % st‐PEA forms an organogel. STM on this gel reveals the formation of helical aggregates on the graphite surface–solution interface with shapes and dimensions matching st‐PEA triple helices, in good agreement with the structures proposed by molecular modeling. X‐ray diffraction, WAXS, SAXS and solid state NMR spectroscopy studies suggest that st‐PEA triple helices are also present in the solid state, up to temperatures well above the melting point of st‐PEA. Formation of higher‐order aggregates explains the observed LC behavior of st‐PEA, emphasizing the importance of the "tertiary structure" of synthetic polymers on their material properties.